Сезонная изменчивость потребления кислорода пластинчатозубой (Nasokia indica Gray) и серой (Rattus norvegicus Berk.) крысами - Смирнов, П.К.; Као Ван Шунг (Вестник зоологии, 1971)
The paper presents the research results of seasonal change s in oxygen consumption of Nesokia indica Gra y and Rattus norvegicus Berk . An interspecific differentiation in energetic exchange between different sex and age groups are noted. A higher охуцеп consumption in Rattus norvegicus is considered as an adaptive peculiarity appeared aa result of life under conditions of cold climate. Both species possess a distinct seasonal dynamics ol oxygen consumption.